Analisis Strategi Pengembangan Pantai Widodo sebagai Objek Wisata Unggulan di Kabupaten Bombana - Midi, La Ode; Kasim, Safril; Sudia, La Baco; Gandri, La; Erif, La Ode Muhammad; Tuwu, Eka Rahmatiah (MAKILA, 2025)
This study aims to formulate development strategies for Widodo Beach as a flagship tourism destination in Bombana Regency. The beach has strong ecotourism potential, characterised by white sandy shores, clear seawater, and a relatively pristine coastal ecosystem. However, current utilisation remains suboptimal due to limited accessibility, inadequate supporting facilities, and insufficient promotional efforts. A mixed-methods approach was employed, integrating qualitative and quantitative techniques. Data were obtained through field observations, interviews with local communities and visitors, and structured questionnaires, and analysed descriptively using a SWOT analytical framework. The results indicate that the main strengths of Widodo Beach lie in its scenic landscape, environmental cleanliness, and the hospitality of local residents. Identified weaknesses include a lack of public facilities, poor road accessibility, and limited destination promotion. Opportunities arise from increasing interest in ecotourism, potential job creation, and growing governmental support, while external threats include coastal environmental degradation and competition from similar destinations in the surrounding area. The strategic position of Widodo Beach falls within the aggressive growth quadrant, necessitating proactive and integrated development strategies. Recommended strategies include improving tourism infrastructure, diversifying attractions, strengthening integrated digital promotion, and fostering active community participation in tourism governance. These findings highlight the importance of a participatory and locally grounded approach to achieving sustainable tourism development. The study offers strategic implications for local governments and stakeholders in formulating ecotourism policies that integrate environmental conservation with community empowerment